#COVID-19 Awareness Video: #IITA Germplasm Health Unit - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
Dr Lava Kumar, Head of Gerplsam Health, and Virology and Molecular Diagnostics, IITA re-iterates the need for strict compliance to management policies for Covid-19 safety.